Comparative assessment on irreversible losses in heat pumps using R744/R32/R1234yf and R744/R32/R1234ze(E). (16th November 2016) - Fukuda, Sho; Kojima, Hideki; Kondou, Chieko; Takata, Nobuo; Koyama, Shigeru
Abstract : This article presents an experimental assessment of coefficient of performance and irreversible loss in the heat pump cycle using hydro-fluoro-olefin base ternary mixtures: YF300 (R744/R32/R1234yf; 4/44/52 mass%), YF200 (R744/R32/R1234yf; 5/28/67 mass%), ZE300 (R744/R32/R1234ze(E); 4/43/53 mass%), and ZE200 (R744/R32/R1234ze(E); 9/29/62 mass%). The smaller volumetric capacity of YF200 and ZE200 increases the irreversible loss caused by the pressure drop with increasing heat load. ZE200, which has a temperature glide of approximately 22 K, increases the irreversible loss in the condenser, evaporator, and expansion valve. The experimental results indicate that YF300 and ZE300 could be potential alternatives to R410A and R32.